Bartter Syndrome Type 1 Presenting as Nephrogenic Diabetes Insipidus - Gianluca Vergine; Elena Fabbri; Annalisa Pedini; Silvana Tedeschi; Niccolò Borsa (Hindawi Limited, 2018)
Bartter syndrome (BS) type 1 (OMIM #601678) is a hereditary salt-losing renal tubular disorder characterized by hypokalemic metabolic alkalosis, hypercalciuria, nephrocalcinosis, polyuria, recurrent vomiting, and growth retardation. It is caused by loss-of-function mutations of the SLC12A1 gene, encoding the furosemide-sensitive Na-K-Cl cotransporter. Recently, a phenotypic variability has been observed in patients with genetically determined BS, including absence of nephrocalcinosis, hypokalemia, and/or metabolic alkalosis in the first year of life as well as persistent metabolic acidosis mimicking distal renal tubular acidosis. We report the case of a child with a genetically determined diagnosis of Bartter syndrome type 1 who presented with a phenotype of nephrogenic diabetes insipidus, with severe hypernatremia and urinary concentrating defect. In these atypical cases, molecular analysis is mandatory to define the diagnosis, in order to establish the correct clinical and therapeutic management.